ANALISIS PELAKSANAAN STRATEGI PEMASARAN PRODUK SEPEDA MOTOR (Kasus Evaluasi Penjualan Pada PT.Yamaha Mahkota III Pekanbaru) - Hermanto, Maiko; Andri, Seno (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
PT. Yamaha Crown III Pekanbaru is one of two dealer Yamaha dealer in the District Peace Marpoyan Pekanbaru, by looking at business opportunities for the brand Yamaha motorcycle sales are becoming the focus of marketing companies. for the brand Yamaha motorcycle sales Pt. Yamaha Crown III tried to make an effort to do the marketing strategy for products marketed a concern for consumers and interested to buy didealer PT. III crown. The implementation of the marketing strategy undertaken by PT. Yamaha Crown III Pekanbaru is the use of the Product Strategy Yamaha only sell products that are of good quality and have good resistance machines and the most important is the production of Yamaha always have an innovative design every year.Transportation is becoming a vital tool even arguably very important because in the age of globalization. Without a means of transportation, we can to waste time just to achieve the goal if we rely on our feet. For now, the means of transport which are very reliable for the middle class, namely motor. And the motor is a mainstay for the fight time uncompromising one is Yamaha. Because many enthusiasts Yamaha then be an opportunity for entrepreneurs to do business selling motorcycle brand Yamaha.The results of the study concluded that the implementation of marketing strategies motorcycle made by PT.Yamaha Crown III Pekanbaru to achieve the goal of increasing sales view of respondents is sufficient enough baik.Artinya company is able to maintain the business while many competitors are quite competitive in marketing their products .Persoalan not achieving sales targets does not mean that firms have experienced kebangkrutan.Akan but the owner of the company to be better at managing the business enterprise, so that the company can continue to survive and thrive.Kunci.Pemasaran said, Strategy, Mix